Intercultural/Pluricultural Communication Construct and Its Levels - Vita Kalnbērziņa (Baltic Journal of English Language, Literature and Culture)
The aim of this article is to explore the intercultural component (IC) in the English language curricula for the secondary and tertiary education in Latvia in the light of the new edition of Common European Framework of Language Learning, Teaching and Assessment Companion Volume with New Descriptors (CEFR, 2017) and compare it with the previous intercultural communication competence. The research method is documentary analysis of the three documents as regards their approach to intercultural communication. The analysis found that the documents were compatible, in spite of the difference of terminology, although CEFR (2017) aims at language users’ sensitivity and awareness in action, the secondary school proposes tolerance and following the rules, the tertiary education curriculum suggests critical thinking and analysis of the cultural phenomena. The roles of the three documents and their development contexts explain these differences and allow each one of the documents to give their own contribution to IC, as long as the users of the documents understand their differences and shortcomings.